Methodology for the simultaneous optimization of location and parameters of friction dampers in the frequency domain. Issue 12 (2nd December 2018) - Miguel, Letícia Fleck Fadel; Miguel, Leandro Fleck Fadel; Lopez, Rafael Holdorf
ABSTRACT: It is well known that the use of passive energy dissipation devices such as friction dampers reduces the dynamic response of structures subjected to earthquakes. However, the parameters of each damper as well as the best position of these devices in the structure remain difficult to determine. Although articles on optimum design of tuned mass dampers and viscous dampers have been published, there is a lack of studies on the optimization of friction dampers. In previous contributions, the authors proposed a method for optimum design of this kind of damper. The proposed method is very useful; however, the computational time required is high. Thus, in this article, a new methodology for the simultaneous optimization of placement and forces of friction dampers is proposed. As this new method is developed in the frequency domain, the computational time is considerably reduced. For this purpose, the search group algorithm, recently developed by the authors, is employed, which is able to deal with optimization problems involving mixed discrete and continuous variables. For illustrative purposes, a six-storey shear building is analysed. Forces and positions of friction dampers are the design variables, while the objective function is to minimize the root mean square displacement at the top of the building. The results showed the excellent performance of the proposed method, reducing the root mean square displacement by more than 82%, with only three friction dampers and in a relatively short computational time.